How Old Is My Dog? Identification of Rational Age Groupings in Pet Dogs Based Upon Normative Age-Linked Processes - Harvey, Naomi D. (Frontiers in Veterinary Science, 2021)
Behavioural development is a lifelong process where cognitive traits such as learning, and memory may be expected to take a quadratic or linear trajectories. It is common practice for operational purposes to reduce study subjects into chronological categories when conducting research. However, there are no agreed upon thresholds for this practice and the lack of standardisation may hinder comparison between studies of normative and pathological ageing. In this perspective review, chronological categories have been identified that can be considered to represent normative cognitive and neurological ageing in domestic family dogs. These categories work to capture age related developmental trajectories for the majority of dog breeds. It is encouraged that researchers studying cognition and behaviour, cognitive pathological deficits, or welfare of dogs across age categories utilise the categories presented here to best enable comparison between studies. The proposed groups could also support education programmes informing owners of what behavioural changes to expect in their dog as they age but they cannot be used to reflect health-based needs associated with breed specific morbidity. Use of the age categories proposed here highlights significant welfare issues for breeds with the shortest average lifespans (e.g. the Great Dane). Studies show that there is no evidence of an increased rate of behavioural or cognitive ageing in short-lived breeds, and the shortest-lived breeds are most likely to die when classified by the proposed categories as Mature Adults. Adoption of these chronological categories in future research would aid comparison between studies and identification of non-normative age-related pathologies.